On the Use of Bovine Serum Albumin for the Spectrophotometric Determination of Protein in Unhopped Wort. (2nd July 2020) - Huerta-Zurita, Ramon; Zamora-Diaz, Mauro
Abstract: Malt soluble protein (SP) can be determined by different analytical procedures such as Kjeldahl, combustion, or spectrophotometry. From a practical standpoint, the spectrophotometric method is the most preferred. This method requires a linear calibration with different malts in a wide SP range. For this calibration however, protein in wort is determined by Kjeldahl as the reference method. Considering that some soluble protein standards could be used as an alternative for the Kjeldahl analysis in the calibration step, the objective of this research was to evaluate the use of bovine serum albumin (BSA) as a protein standard in the determination of SP. Results showed that the BSA standard curve overestimates protein in wort and, therefore, SP values. However, estimated vs. actual wort protein values were highly associated ( R 2 =0.9984) and the correspondent regression lines had similar slopes. Taking this into account, the BSA standard curve was adjusted with wort protein values observed in international malt check samples (SP range= 4.3–6.4% of malt, dry basis). The resultant equation from the BSA adjusted curve [wort protein, %wt/vol= (1.4007* A 215-225 ) − 0.0071] improved the estimation of protein in wort by minimizing differences in magnitude.